(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
Flax is an important industrial crop known for its high-quality fibres and various applications in textiles, composites, pulp and paper, and other industries. This study investigates the impact of sowing time and phenological stages on fibre yield and chemical composition of different flax genotypes. Four genotypes: BARI Tishi-1, BD-10708, Canada and China were grown under various sowing times, and fibre yield, cellulose, lignin, hemicellulose and extractives were evaluated. Sowing on November 16 produced the highest fibre yield, with early sowing leading to reduced yield. Analysis of chemical composition at flowering and post-flowering stages revealed significant variation in cellulose, lignin, hemicellulose, and extractive contents across genotypes. BARI Tishi-1 and China demonstrated high and stable α-cellulose levels, particularly in later plantings and post-flowering stages. However, Canada had high extractive and hemicellulose contents. The findings underscore the importance of optimizing sowing time to maximize fibre yield and quality, which is essential for meeting industrial standards and improving the economic value of flax. Bangladesh J. Sci. Ind. Res. 60(1), 45-52, 2025